Perilaku Ibu Hamil Dalam Pelaksanaan P4K Berhubungan Dengan Kesiapan Ibu Hamil Menghadapi Komplikasi - Jannah, Miftakhul; Cahyani, Desy Dwi; Triningsih, Reni Wahyu; Wulandari, Lisa Purbawaning (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2020)
One of the efforts to prevent delays in handling complications is the birth planning and complications prevention program (P4K). If every pregnant woman implements P4K, it is hoped that if complications occur in her pregnancy, she will be able to handle it as early as possible. The purpose of this study was to analyze the relationship between the behavior of pregnant women in implementing P4K and the readiness of pregnant women to face complications in the Kedok Village, the working area of ??Puskesmas Turen. This study used a correlational study design with a cross-sectional approach, a population of 45 pregnant women, and the sampling using simple random sampling technique with a sample size of 40 pregnant women who had met the inclusion criteria, namely pregnant women who had received an explanation about P4K and already had P4K stickers, willing to be respondents. The research instrument used a questionnaire on the behavior of pregnant women in implementing P4K and a questionnaire on the readiness of pregnant women to face complications. Data analysis used the chi-square test with a significance level of ? 0.05. The results showed a relationship between the behavior of pregnant women in implementing P4K and the readiness of pregnant women to face complications (p-value <0.001). Pregnant women can carry out P4K as an effort to increase the readiness of pregnant women in facing possible complications. Keywords: Pregnant Mother Behavior, P4K, Readiness, Complications